2010
DOI: 10.1063/1.3478012
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of junctionless Si nanowire transistors with 3 nm gate length

Abstract: Access to the full text of the published version may require a subscription. Rights

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 13 publications
3
48
0
Order By: Relevance
“…Finally, the source-drain tunneling currents of the devices for the two doping profiles are around 0. that is, FETs with homogeneous source-channel-drain doping similar channel dimensions and NW orientation. Supporting our previous findings, 25 this suggests that at such scales the distribution of charge carriers around the dopant blurs the boundaries of a junction over a distance comparable to the channel length. Therefore, besides being very difficult to fabricate, junctioned FET designs at this scale will fail to effectively keep carriers out of the channel in the off-state.…”
Section: A Transport Propertiessupporting
confidence: 74%
See 1 more Smart Citation
“…Finally, the source-drain tunneling currents of the devices for the two doping profiles are around 0. that is, FETs with homogeneous source-channel-drain doping similar channel dimensions and NW orientation. Supporting our previous findings, 25 this suggests that at such scales the distribution of charge carriers around the dopant blurs the boundaries of a junction over a distance comparable to the channel length. Therefore, besides being very difficult to fabricate, junctioned FET designs at this scale will fail to effectively keep carriers out of the channel in the off-state.…”
Section: A Transport Propertiessupporting
confidence: 74%
“…Over the last decade, the description of electronic quantum transport based on computational methods has become one of the core topics in atomic-scale modeling and device simulations, 20 and the explicit electronic structure of materials has been considered from approximate methods that use empirical bulk parameterization 15 to first-principles approaches, [21][22][23] and approximations thereof. 13,[23][24][25] In this paper, we first discuss our own quantum transport implementation (TiMeS-Transport in Mesoscopic Systems). Separating the step that provides the electronic structure description from the transport module, TiMeS offers a crossplatform solution that allows efficient calculations of materials transport properties and realistic device simulations to extract current-voltage and transfer characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…8 Atomic-scale simulations have confirmed the scalability of JNTs down to sub-5 nm dimensions. 9 Several recent publications on the characterization of JNTs and comparison of these devices with conventional IM devices can be found in the literature. [10][11][12][13][14][15][16][17][18] Germanium inversionmode (IM) devices have been previously investigated 19,20 but no quantum mechanical study on the performance comparison of germanium and silicon JNTs has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial amount of theoretical work has been done in studying the performance of trigate FETs and nanowires. This work ranges from semi-classical transport studies [4] to full-band quantum transport analysis [5].…”
Section: Introductionmentioning
confidence: 99%
“…A substantial amount of theoretical work has been done in studying the performance of trigate FETs and nanowires. This work ranges from semi-classical transport studies [4] to full-band quantum transport analysis [5].Substantial work on the impact of random discrete dopants on the performance of MOSFET transistors has been carried out [6][7][8][9][10]. This work has made use of Drift-diffusion, Monte Carlo and the Non-Equilibrium Green function (NEGF) carrier transport models.…”
mentioning
confidence: 99%